Efficient Identification of the Forest Tree Species in Aceraceae Using DNA Barcodes - Han, Yu-Wei; Duan, Dong; Ma, Xiong-Feng; Jia, Yun; Liu, Zhan-Lin; Zhao, Gui-Fang; Li, Zhong-Hu (Frontiers in Plant Science, 2016)
Aceraceae is a large forest tree family that comprises many economically and ecologically important species. However, because interspecific and/or intraspecific morphological variations result from frequent interspecific hybridization and introgression, it is challenging for non-taxonomists to accurately recognize and identify the tree species in Aceraceae based on a traditional approach. DNA barcoding is a powerful tool that has been proposed to accurately distinguish between species. In this study, we assessed the effectiveness of three core standard markers (matK, rbcL and ITS) plus the chloroplast locus trnS-trnG as Aceraceae barcodes. A total of 231 sequences representing 85 species in this forest family were collected. Of these four barcode markers, the discrimination power was highest for the ITS (I) region (50%) and was progressively reduced in the other three chloroplast barcodes matK (M), trnS-trnG (T) and rbcL (R); the discrimination efficiency of the ITS marker was also greater than any two-locus combination of chloroplast barcodes. However, the combinations of ITS plus single or combined chloroplast barcodes could improve species resolution significantly; T+I (90.5% resolution) and R+M+T+I (90.5% resolution) differentiated the highest portion of species in Aceraceae. Our current results show that the nuclear ITS fragment represents a more promising DNA barcode marker than the maternally inherited chloroplast barcodes. The most efficient and economical method to identify tree species in Aceraceae among single or combined DNA barcodes is the combination of T+I (90.5% resolution).